NanoMaterialsCAD: Flexible Software for the Design of Nanostructures. Issue 1 (30th November 2020) - Nikoulis, Giorgos; Grammatikopoulos, Panagiotis; Steinhauer, Stephan; Kioseoglou, Joseph
Abstract: NanoMaterialsCAD is a new open source tool dedicated to the creation, manipulation, and 3D visualization of crystalline structures at the nanoscale. It is designed for preprocessing atomistic configurations to be used as input for atomistic (e.g., molecular dynamics or Monte Carlo) or ab initio (e.g., density functional theory) computer simulations. It offers several tools for designing complex nanostructures (including nanoparticles, nanowires, nanotubes, nanoscrolls, etc., and combinations/permutations of them) which are either lacking or cumbersome in other existing packages. Through its intuitive graphical user interface (GUI) it enables facile ways to design and modify the size/shape and relative positions of nanoobjects while observing the changes in real time. NanoMaterialsCAD is written in C++, and exploits Open Graphics Library (OpenGL) (for the GUI), Win32API (for interaction with Windows), and Assembly (for fast data management). The source code and executable file are available for download from GitHub (https://github.com/cossphy/NanoMaterialsCAD ). It is aspired that NanoMaterialsCAD will be adopted by the nanomaterials modeling community as a valuable resource; to this end it will be kept improving, incorporating more nanostructures, and adding extra functionalities to its toolbox. Abstract : NanoMaterialsCAD is a new open source tool dedicated to the creation, manipulation, and 3D visualization of crystalline structures at the nanoscale. It is designed for preprocessing atomistic configurations to be used as input for atomistic (e.g., molecular dynamics or Monte Carlo) or ab initio (e.g., density functional theory) computer simulations. It offers several tools for designing complex nanostructures (including nanoparticles, nanowires, nanotubes, nanoscrolls, etc., and combinations/permutations of them).